Strategizing quality implementation in intensive care unit: a statistically-sound, novel approach using Delphi technique - Rinkoo, Arvind Vashishta; Kaur, Ramanjeet; Singh, Garima; Dubey, Karuna; Masih, Leela; Chandra, Hem (International Journal of Research in Medical Sciences, 2017)
Background: Ascendancy of Intensive Care Medicine in the realm of healthcare has made Continuous Quality Improvement (CQI) in Intensive Care Units (ICUs) most imperative for hospital administrators worldwide. Perspicuous identification of all clinical and non-clinical drivers warranting contemplation is the most arduous step in achieving the same. This study avers the effectiveness of a statistically-sound, novel approach using Delphi technique in identifying various drivers to be prioritized for strategizing CQI in the postoperative ICU of a premier tertiary care hospital in Asia. Methods: Three rounds of Delphi survey were initially planned. Mean Rank Scores (MRS) was used to rank the opinions in this study. Results: Statistically validated consensus was reached among expert participants on five drivers that should galvanize hospital administration vis-à-vis strategizing quality implementation in the post-operative ICU. Foremost among these was adequate staff that is tantamount to desirable staff-patient ratio (MRS: 9.4), and regular medical audit for sustainable quality in healthcare delivery (MRS: 9.1). Experts further concurred that communication skills of ICU staff (MRS: 8.9), continuous medical education and training of these staff (MRS: 7.6) along with perspicuous ‘Standard Operating Procedures’ (MRS: 7.1) were other points to be considered. Conclusions: With regard to the process of planning, identification of correct drivers holds the crux in strategizing quality implementation in any setup. Implementing change management is equally imperative. This approach can be used to realize both of these.